Analysis of a workstation in an agricultural equipment factory: study of movement and layout - Lima , Katiucya Juliana Rodrigues de; Resende, André Alves de (Brazilian Journal of Production Engineering, 2023)
The work environment must facilitate and favor the realization of the activities, in order to generate productivity and efficiency. Therefore, the purpose of this study is to analyze the worker’s flow and movement at a welding station of an agricultural equipment factory, based on time study and layout. The main objective is to minimize the unnecessary movement and time spent on the daily activities of this workstation. It is an applied research project, descriptive and qualitative. To be developed, the Sequence of Events was considered, where the transport activities were identified and analyzed through the From-To Chart, Relationship Chart and Proximity Diagram, besides concepts of layout and material flow. Some modifications were suggested on the display of storage locations and through simulation because it was verified that the changes would apply on traveled distances and time decreases, meeting this study purpose. The comparison between the current scenario and the proposed one was made, showing the possible gains for the company and demonstrating the importance of studies like these inside of the organizations.